GENERATING AND CHARACTERISTIC OF SURFACES IN MECHANICAL MACHINING OF MICRO-PARTS - Branislav SREDANOVIC; Gordana GLOBOCKI-LAKIC; Damir GRGURAS; Davorin KRAMAR; Franci PUSAVEC (Proceedings on Engineering Sciences, 2019)
Development of micro-devices parts is intensified with developments in medical device and energetic industry. In production of micro-parts (micro-pump, micro-gears, micro-manipulators, etc.), a wide range of engineering materials is encountered. Strict requirements are set in terms of characteristic of micro-parts machined surfaces, such are low surface roughness, advanced tribological characteristic, etc. In this paper is analysed possibilities of different metallic materials mechanical micro-machining. The analysis includes the analysis of the generating and characteristics of the machined surfaces, and influence of a whole set of parameters on surface characteristic. The results showed the benefits of mechanical micromachining and proved that it can achieve satisfactory results of the surface characteristics indicators.